2007
DOI: 10.1007/s00520-006-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ needs assessment in cancer care: a review of assessment tools

Abstract: There is a need to continue to develop and test tools that have the attributes necessary for effective practice and to research their effects on the quality of supportive cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
193
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(208 citation statements)
references
References 46 publications
(37 reference statements)
0
193
0
15
Order By: Relevance
“…Additionally, the findings revealed a lack of strategy for a common database for registering the effects of the assessments of rehabilitation needs across the sectors and regions that had been set in motion. This finding is supported by Richardson et al (2007) in a British review showing that there is a dearth of evaluations of the viability of measurement tools, professional clinical applicability and the effects on patient outcomes [24]. Rehabilitation of cancer patients should be set up to include evaluation and organized on an evidence base.…”
Section: Dt Not Integrated In From Patients' Treatment Protocolmentioning
confidence: 96%
“…Additionally, the findings revealed a lack of strategy for a common database for registering the effects of the assessments of rehabilitation needs across the sectors and regions that had been set in motion. This finding is supported by Richardson et al (2007) in a British review showing that there is a dearth of evaluations of the viability of measurement tools, professional clinical applicability and the effects on patient outcomes [24]. Rehabilitation of cancer patients should be set up to include evaluation and organized on an evidence base.…”
Section: Dt Not Integrated In From Patients' Treatment Protocolmentioning
confidence: 96%
“…Needs of patients with various cancer diagnoses are often assessed with a variety of questionnaires constructed for people with cancer [7]. Most instruments include a wide range of items covering various need domains, with respondents being asked to rate their level of need for each item.…”
mentioning
confidence: 99%
“…To guide the assessment process and to operationalize its content, several authors have suggested structuring the information collection with the help of various tools such as questionnaires or interview guides (Richardson, Medina, Brown, & Sitzia, 2007;Wen & Gustafson, 2004). In Quebec, PNOs have been using since 2013 a standardized form entitled "Évaluation initiale du client suivi en oncologie" [Oncology Patient Assessment] to guide their interviews and collate their information (Fournier et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…As none of these tools are able to pinpoint the population's needs on their own, an approach combining self-administered questionnaires, a semi-structured interview and tools speci c for certain conditions is recommended (Richardson et al, 2007;Wen & Gustafson, 2004). Thus, the assessment process is primarily based on a person-centred approach to establish a therapeutic relationship and draws upon knowledge, clinical skills and the use of speci c tools.…”
Section: Discussionmentioning
confidence: 99%